Kelengkapan Rekam Medis Di Poli Umum Rawat Jalan Di Rumah Sakit Santa Elisabeth Medan - Purba, Elsa Indriani; Simbolon, Pomarida; Ginting, Nasipta (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient, and emergency services. Objective: to determine the completeness of medical records on patient identity, anamnesis, informed consent, medical resume in outpatients. Method: descriptive research with a simple random sampling technique of medical record files. The population is all medical record files of outpatients in the polyclinic totaling 2139 files. The sample to be studied is 91 outpatient medical records using a simple random sampling method. The dependent variable is the completeness of medical record files, namely patient identity, anamnesis, informed consent, medical resume, Data collection tools use a checklist sheet. The analysis method uses editing, coding, scoring and tabulating. Results: obtained percentage of completeness of medical records based on patient identity of 84.6%, anamnesis 94.5%, informed consent 52.7%, medical resume 61.5%, completeness of medical records as a whole 90.1%. The percentage of incomplete medical records based on patient identity was 15.4%, Medical Records based on anamnesis 5.5%, medical records based on Informed Consent 47.3%, medical records based on Medical Resume 38.5%, completeness of medical records overall 90.1%. Conclusion: The completeness and incompleteness of outpatient general polyclinic medical record files are due to lack of communication between health workers in filling out medical record files.